Amalgamation Schemes : Antiblackness and the Critique of Multiracialism - Sexton, Jared (Associate Professor) (Book collections on Project MUSE., 2008)
Despite being heralded as the answer to racial conflict in the post-civil rights United States, the principal political effect of multiracialism is neither a challenge to the ideology of white supremacy nor a defiance of sexual racism. More accurately, Jared Sexton argues in Amalgamation Schemes, multiculturalism displaces both by evoking long-standing tenets of antiblackness and prescriptions for normative sexuality. In this timely and penetrating analysis, Sexton pursues a critique of contemporary multiracialism, from the splintered political initiatives of the multiracial movement to the ac.